Identifikasi Pemasaran Pariwisata Hijau di Kawasan Ekowisata Mangrove Wonorejo, Kota Surabaya - Nadi Chrissanty; I Nyoman Sukma Arida (JURNAL DESTINASI PARIWISATA, 2020)
Kawasan Ekowisata Mangrove Wonorejo (KEMW) is one of the tourist mangrove forests located in the East Coast region of Surabaya. The purpose of this field research was to identify tourism products owned by KEMW, as well as to analyze the form of product marketing that had been implemented in the KEMW. The analytical method in this study uses a type of qualitative-descriptive analysis, namely research that describes or describes the object of research based on facts that appear or as they are. The data sources used are derived from primary data and secondary data. Theories and concepts used are the concept of ecotourism, the definition of mangrove forests, the concept of tourism products, the limits of the definition of marketing, and the concept of Green Tourism Marketing (GTM). The results of this study explain that KEMW has 3 (three) main attractions Environmental Education Tourism, Sport Tourism, and Culinary Tourism and Other Local Products, with 4 (four) zones namely Mangrove Zone, Tourism Zone, Recipient Zone and Support Zone. KEMW has sufficient supporting facilities and in terms of accessibility, KEMW is easily accessible both in terms of information and accommodation. Based on the application of the concept of Green Tourism Marketing (GTM), KEMW has fulfilled almost all indicators, both in terms of local communities, tourists, government, and local tourism businesses. KEMW is also considered to have succeeded in applying the concept of ecotourism that pays attention to ecological conditions and focuses on sustainable tourism. Keyword: Ecotourism, Kawasan Ekowisata Mangrove Wonorejo, Green Tourism Marketing